Unknown sources of history first Polish Roman Catholic parish in Kharkiv - Зайонц, Єжи (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”)
The article is a contribution to the history of the first Polish Roman Catholic parish in Kharkiv, which operated in the city in the midst of other religious communities. They alluded each other close contacts, take joint actions to larger communities significantly raising the spiritual culture of the leading urban center of Eastern Ukraine. The author analyzes the magazine "Parafia Charkowska", which was the end of 1,910 years to the first quarter of 1911 years extension of the pulpit of the church at ul. Gogol in Kharkov, and its columns were used for the publication of pastoral letters Archbishop, decrees of the Congregation for the Vatican, materials preaching about the benefits of physical and spiritual subject, or the establishment of a national youth. It was a mirror reflecting the oldest history of the local church, was finally chronicle of current events and the kind of book baptized, marriages and deceased Catholics Kharkiv.